Inheritance of Yield Related Traits in a Half Diallel Crosses of Some Maize (Zea mays L.) Genotypes (The Agriculturists, 2020)
Inheritance of grain yield, heterosis and combining ability were investigated in maize populations obtained from half-diallel crossing among six inbred parental lines. General (GCA) and specific (SCA) combining ability effects were significantly different among parental lines. The grain yield was under the partial gene effect. The parents P1, P3 and P5were considered suitable according to their yield contributing attributes couple with general combining ability effects. The midparentheterosis values ranged from -27.246 (P2 xP5) to 15.209% (P1 xP2) whereas the better parent heterosis values varied between 22.375(P2x P3) to 40.363% (P2 x P5) only seven crosses had higher grain yields. Of those crosses, P1×P2, P2×P5 and P1×P3 were considered most promising hybrids yielding heterosis as 15.880%, 20.363% and 40.363 respectively over their parents.The Agriculturists 2020; 18(1) 18-25